PENGABDIAN DAN PEMBERDAYAAN UNTUK MENINGKATKAN EKSPOR PRODUK FASHION/PERHIASAN DI ERA DIGITAL - Ni Made Ida Pratiwi; Irgi Putri Olivia (Pojok Publisher, 2024)
Technological developments are closely related to the trading system, especially export activities. Developing technology with various existing applications is the right choice because it makes international trade increasingly have a very broad market coverage. Export activities for an MSME apart from needing media that makes the MSME more known to more people and more widespread, it also needs a place as a forum for training and information about digitalization. PT. Lacorre Loka Maya is a digitally oriented learning institution that organizes community service activities through the Digital Export of Spices and Fashion training program. This training aims to produce young exporters who can develop local products in the spice and fashion sectors so they are ready to enter the global market. The results of community service activities through the Digital Export of Spices and Fashion program have increased community skills in using technological development with various applications to produce young exporters who can develop local products in the spice and fashion sectors.